1997
DOI: 10.1021/ja9708629
|View full text |Cite
|
Sign up to set email alerts
|

Li and Na Diffusion in TiO2 from Quantum Chemical Theory versus Electrochemical Experiment

Abstract: Diffusion of Li and Na ions in TiO 2 , anatase, has been studied using theoretical (quantum chemical ab initio periodic Hartree-Fock and a modified semiempirical INDO) as well as electrochemical (chronocoloumetry) methods. On the basis of the theoretical calculations, the geometry of equilibrium and transition states for the impurities as well as the crystalline framework are analyzed and discussed. The calculated activation energies for Li + and Na + diffusion were found to be only slightly higher than 0.5 eV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
185
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 226 publications
(215 citation statements)
references
References 31 publications
30
185
0
Order By: Relevance
“…The calculated GGA+ U diffusion barriers of ϳ0.6 eV agree with experimental values due to Lunell et al 49 who reported a diffusion barrier of 0.6Ϯ 0.1 eV. The GGA value of 0.511 eV is still compatible with this range, although lies at the limits of the experimental data.…”
Section: F Lithium Diffusion and The Effect Of The LI + -E − Interacsupporting
confidence: 88%
See 3 more Smart Citations
“…The calculated GGA+ U diffusion barriers of ϳ0.6 eV agree with experimental values due to Lunell et al 49 who reported a diffusion barrier of 0.6Ϯ 0.1 eV. The GGA value of 0.511 eV is still compatible with this range, although lies at the limits of the experimental data.…”
Section: F Lithium Diffusion and The Effect Of The LI + -E − Interacsupporting
confidence: 88%
“…49,79 The strength of the interaction between the Li + and Ti 3+ is, however, predicted to be much weaker than suggested by previous atomistic simulations, 27,79 which would indicate the dual Li-electron motion is less strongly correlated than predicted previously. Depending on the strength of the Li + -Ti 3+ interaction, and the effect this has on the relative diffusion barriers for a bound Li + -Ti 3+ and a well separated Li + , it may be possible to probe this difference with suitable experiments.…”
Section: Summary and Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Amongst them, anatase TiO2 which was previously investigated as a lithium-ion host material in LIBs due to its low price, high safety, non-toxicity, abundance in the earth's crust, and negligible volume change(<4%) during Li + insertion/extraction [20][21][22][23][24][25][26], has attracted great attention. Yet the reports on TiO2 as Na anode material are quite limited up to date [23,[27][28][29]. Nevertheless the theoretical study by Hagfeldt et al demonstrated the activation barrier for sodium insertion into the TiO2 anatase crystal lattice was supposed to be close to that for lithium which indicates promising candidate role of TiO2 in NIBs considering the large sodium ionic radius [27]. )…”
Section: Introductionmentioning
confidence: 99%